The effect of intervention based on adapted mental health literacy curriculum on attitude and help-seeking intention in high school students in Iran - Zahra Saboohi; Mahnaz Solhi; Mozhgan Lotfi; Malihe Nasiri (Journal of Education and Health Promotion)
Background: Adolescent mental health is a major public health concern in Iran, with 1 of every 5 adolescents suffering from a mental disorder. Mental health literacy (MHL) is an important factor in improving mental health outcomes. To address this issue, a mental health literacy school curriculum used in Canada was adapted, piloted, and evaluated for use in Iranian schools. This study examines the impact of the intervention on the attitude and help-seeking intentions of first and secondary students in Iran. Materials and Methods: This study is semiexperimental research that was conducted on 200 female teenagers who were studying in girls’ secondary schools in Saveh, Central part of Iran, in 2023. The participants were divided into two groups, namely, the intervention group and the control group. Both groups completed a valid and reliable questionnaire that assessed their attitude and help-seeking intention at two different time points. To evaluate the intervention’s effects, a repeated-measures analysis of variance (ANOVA) was used. Results: The study used the repeated-measures ANOVA to assess the changes in the mean attitude and help-seeking intention scores between the intervention and control groups. The findings indicated significant improvements in the attitude of help-seeking (P < 0.001), informal help-seeking intention (P < 0.001), and formal help-seeking intention (P < 0.001) for the intervention group as compared to the control group during the study. Conclusion: The adapted mental health literacy school curriculum has been used and evaluated for the first time in Iran, and it has shown a significant increase in attitude and help-seeking intention among first and secondary female students. These results need to be confirmed by further studies, which should also analyze the interrelationships between different dimensions of mental health knowledge and help-seeking practices. Keywords for this study include mental health literacy, help-seeking, attitude, and female students.